Exploring the Business Model Canvas in the Development of Fashion Products: A Case Study of Rahayu Akar Wangi in Garut - Nurindah, Mandhe Sekar; Puspitasari, Feny (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2023)
Vetiver fashion is a souvenir product from Garut that uses weaving techniques to process the Vetiver. This product is in great demand by tourists when visiting Garut. It gives Vetiver weaving great potential in Indonesia's competition for fashion product innovation. In this study, marketing and product sales were carried out only verbally or through a preorder system, which made this product less well-known in the digital era. The business model canvas is a way to package marketing and product development to fit the target market. A descriptive qualitative method will describe what must be considered to be able to compete in sales according to the needs of the target market.